Laser thermal anneal formation of atomically‐flat low‐resistive germanide contacts. Issue 1 (9th December 2013) - Huet, K.; Shayesteh, M.; Toqué‐Tresonne, I.; Negru, R.; Daunt, C. L. M.; Kelly, N.; O'Connell, D.; Yu, R.; Djara, V.; Carolan, P.; Petkov, N.; Duffy, R.; et al.
Abstract In this work, state‐of‐the‐art laser thermal annealing (LTA) is used to form germanide contacts on n‐doped Ge, and is compared to results generated by rapid thermal annealing (RTA). Surface topography, interface quality, crystal structure, and material stoichiometry are explored for both techniques. For electrical characterization, specific contact resistivities ϱc are extracted. It is shown that LTA can produce a uniform contact with a remarkably smooth substrate interface, with ϱc 2‐3 orders of magnitude lower than the equivalent RTA case. A ϱc of 2.84×10‐7 Ω.cm2 is achieved for optimized LTA parameters. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)